2017
DOI: 10.5194/hess-21-1895-2017
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal thermal regime and climatic trends in lakes of the Tibetan highlands

Abstract: Abstract. The hydrology of the lake-rich Tibetan Plateau is important for the global climate, yet little is known about the thermal regime of Tibetan lakes due to scant data. We (i) investigated the characteristic seasonal temperature patterns and recent trends in the thermal and stratification regimes of lakes on the Tibetan Plateau and (ii) tested the performance of the one-dimensional lake parameterization scheme FLake for the Tibetan lake system. For this purpose, we combined 3 years of in situ lake temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 59 publications
(73 reference statements)
5
51
0
Order By: Relevance
“…FLake was forced with an ensemble of continuous 21st century climate projections from the Coordinated Regional climate Downscaling Experiment for Europe (EURO-CORDEX; Kotlarski et al, 2014). The climate projections were based on an intermediate greenhouse gas concentration trajectory (RCP4.5), representing a moderate climate warming scenario with an end-of-century, top-of-the-atmosphere radiative forcing of 4.5 W m −2 compared to the pre-industrial period (IPCC, 2014).…”
Section: Climate Warming Scenariosmentioning
confidence: 99%
“…FLake was forced with an ensemble of continuous 21st century climate projections from the Coordinated Regional climate Downscaling Experiment for Europe (EURO-CORDEX; Kotlarski et al, 2014). The climate projections were based on an intermediate greenhouse gas concentration trajectory (RCP4.5), representing a moderate climate warming scenario with an end-of-century, top-of-the-atmosphere radiative forcing of 4.5 W m −2 compared to the pre-industrial period (IPCC, 2014).…”
Section: Climate Warming Scenariosmentioning
confidence: 99%
“…Although surface water temperature (T s ) is perhaps the most predictable indicator of warming (Adrian et al, 2009), trends in T s remain globally highly variable (O'Reilly et al, 2015). Deep water temperatures respond less predictably to warming and have been observed to increase, decrease or not change with increasing air temperature (Dokulil et al, 2006;Ficker et al, 2017;Kirillin et al, 2013;Kirillin et al, 2017;Richardson et al, 2017;Winslow et al, 2017). Stratification strength and duration generally increase due to warming (Butcher et al, 2015;Kirillin, 2010), but patterns of change may have little regional coherence and cannot be reliably inferred from surface water trends (Read et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The present modeling experiments indicated that the largest uncertainty for QTP lake ice modeling is the effect of F w . Thermokarst lakes on the QTP are typically shallow and small, without significant surface water input and output, implying that through-lake current or lake-wide circulation under the ice cover are negligible (Kirillin et al, 2015). A cold sediment layer limits the heat release into the overlying water (Lin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the thermal regimes of lakes in the QTP and their impacts on the atmosphere boundary layer and surrounding permafrost during wintertime (ice-covered season) remain unclear. Because of sparse field observations, there is an increasing need for models and parameterizations to better understand the lake-air interaction and lake thermal regime (Kirillin et al, 2017;Wang et al, 2015;Wen et al, 2015).…”
mentioning
confidence: 99%